Penerapan Alat Bukti Dalam Sistem Pembuktian Tindak Pidana Penipuan - Dwi Yulian Widodo; Fathur Rachman; Ino Susanti (VIVA THEMIS, 2018)
Many people take advantage of the situation by misusing the means of cellular technology communication, one of which is a crime that is a fraud that often occurs today is fraud by using sophisticated technology tools such as cellular phones by utilizing Short Message Service services. The problem that will be discussed is how is the application of evidence in the system of proof of fraud and whether the supporting factors and inhibiting factors in the application of evidence in the system of evidence of criminal acts of fraud.This legal research method uses a type of normative descriptive legal research, approach to the problem and this study uses a normative juridical approach and an empirical juridical approach. The type of data is primary data and secondary data. Data sources are secondary data, tertiary primary data. Data collection with literature studies, field studies. Data processing is carried out including data selection and data classification. Data analysis used is qualitative analysis.From the results of this study the authors found that the application of evidence in the system of proof of criminal acts of fraud is that the truth must be tested by means of evidence thus, the means and strength of evidence basically inherent in each evidence found. Supporting factors in the application of this evidence must be cooperation between legal institutions and providers of cellular telephone networks and the active role of victims in resolving fraudulent crimes. The inhibiting factors in the application of this evidence are the lack of facilities and infrastructure at the Lampung Police's special cyber unit, the next obstacle if the perpetrators did not leave their last GPS cellphone, so the Lampung cyber police could not find out where the perpetrators of the fraud were. The conclusion is that an act can be said to be criminal fraud if the elements are fulfilled according to the Law. In carrying out the verification of fraud through SMS, besides supporting factors in the form of a cyber police team, the task is specifically to deal with cyber crime.